Pengaruh Bimbingan Orang Tua Terhadap Minat Membaca Peserta Didik Kelas IV di SDK Ndona 2 Kecamatan Ndona Kabupaten Ende - Virgilius Bate Lina; Berty Sadipun (Jayapangus Press, 2021)
The objectives of this study were: (1) To determine parental guidance on reading interest of fourth grade students at SDK Ndona 2, Ndona District, Ende Regency. (2) This is to determine the reading interest of fourth grade students at SDK Ndona 2, Ndona District, Ende Regency after receiving guidance from parents. (3) To determine the effect of parental guidance on reading interest of fourth grade students in SDK Ndona 2, Ndona District, Ende Regency. This type of research used in this research is a type of quantitative correlation research with the research approach used is descriptive statistics. Research on the effect of parental guidance on students' reading interest was carried out at SDK Ndona 2, Ndona District, Ende Regency. The research subjects were all fourth grade students at SDK Ndona 2. The variables and indicators in this study were the independent variables or influence variables, namely parental guidance and the dependent variable or the affected variable, namely reading interest. Data collection techniques using a questionnaire (questionnaire) and documentation. The data analysis technique used in testing the hypothesis is the product moment correlation technique. The results of the research from the calculation of the correlation using the product moment correlation technique between the X and Y variables, namely the magnitude of the influence of parental guidance on reading interest from the results. The R Square value of 0.939 is between 0.80 - 1,000, so the effect of parental guidance on students' reading interest is very strong. . If interpreted as percentage it is 93.9% while the rest is 6.1% which is influenced by other factors outside the parental guidance variable. So the hypothesis which says that there is an effect of parental guidance on reading interest of grade IV students in SDK Ndona 2 is accepted. Thus it is suggested for parents of students to better supervise and take the time to guide students to learn to read at home and limit the playing hours of students so that more time is spent learning to read at home, so as to increase students' reading interest.